Reoperative Partial Nephrectomy—Does Previous Surgical Footprint Impact Outcomes?. Issue 3 (27th September 2021) - Gurram, Sandeep; Friedberg, Nicholas A.; Gordhan, Chirag; Li, Winston; Ahdoot, Michael A.; Egan, Jillian; Yerram, Nitin K.; Bratslavsky, Gennady; Metwalli, Adam R.; Linehan, W. Marston; Ball, Mark W.
Abstract : Purpose: Historically, open techniques have been favored over minimally invasive approaches for complex surgeries. We aimed to identify differences in perioperative outcomes, surgical footprints, and complication rates in patients undergoing either open or robotic reoperative partial nephrectomy. Materials and Methods: A retrospective review of patients undergoing reoperative partial nephrectomy was performed. Patients were assigned to cohorts based on current and prior surgical approaches: open after open, open after minimally invasive surgery, robotic after open, and robotic after minimally invasive surgery cohorts. Perioperative outcomes were compared among cohorts. Factors contributing to complications were assessed. Results: A total of 192 patients underwent reoperative partial nephrectomy, including 103 in the open after open, 10 in the open after minimally invasive surgery, 47 in the robotic after open, and 32 in the robotic after minimally invasive surgery cohorts. The overall and major complication (grade ≥3) rates were 65% and 19%, respectively. The number of blood transfusions, overall complications, and major complications were significantly lower in robotic compared to open surgical cohorts. On multivariate analysis, the robotic approach was protective against major complications (OR 0.3, p=0.02) and estimated blood loss was predictive (OR 1.03, p=0.004). Prior surgical approach was not predictive for major complications. Conclusions: Reoperative partial nephrectomy is feasible using both open and robotic approaches. While the robotic approach was independently associated with fewer major complications, prior approach was not, implying that prior surgical approaches are less important to perioperative outcomes and in contributing to the overall surgical footprint.